Academic Senate Minutes 2001-02-08 - Academic Senate:::::::::
Agenda modified and approved. Minutes from 12/7/00 approved. Announcements regarding Mayors visit and Ad Hoc Faculty Housing Committee. Election nominations report. "The CSU at the Beginning of the 21st Century: Achieving the Highest Levels of Quality and Meeting the Needs of California" document presented and discussed. First Reading of Resolution on vote of No Confidence in Chancellor Reed from P. Phillips. First Reading on Senate Budget Committee proposal. Feedback sought from faculty for Accountability Report for Chancellor's Office.